THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON IMPROVING THE CAPABILITIES OF UMKM: A LITERATURE STUDY - Loso Judijanto; Iyad Abdallah Al- Shreifeen (ADISAM Publisher, 2024)
This study aims to examine the effect of entrepreneurial education on improving the capabilities of Micro, Small and Medium Enterprises (MSMEs). In the context of a dynamic global economy, MSMEs play a vital role in economic growth, job creation and innovation. However, MSMEs face various challenges including limited access to resources, managerial knowledge, and technology. Entrepreneurial education is positioned as an important tool to overcome these challenges and improve the capabilities of MSMEs. This research uses the literature study method by compiling and analysing data from various bibliographic sources related to the topic. The results show that entrepreneurship education has a significant influence on improving the managerial, operational, financial and strategic capabilities of MSMEs. It provides new insights, expands networks, and facilitates the adoption of innovations and technologies. This research underscores the importance of policies and programmes that support the development of entrepreneurship education as a strategic measure to strengthen the MSME ecosystem. The practical implication of the findings is the need for interventions designed to provide entrepreneurial education and training inclusively to MSME owners and managers, so that they can contribute to the achievement of sustainable economic growth.